Adhesive elastic tape modifies forefoot motion in young women with flatfoot - Maikon Gleibyson Rodrigues dos Santos; Darlan Martins Ribeiro; Frederico Igor Ribeiro Calaça; Marcelo Klafke; Thiago Vilela Lemos; João Paulo Chieregato Matheus (Termedia Publishing House, 2024)
Purpose Flatfoot has been associated with an increased risk of lower limb injuries. Therefore, it is crucial to assess the efficacy of therapeutic interventions focused on foot realignment. This study aimed to investigate the effect of elastic tape on the motion of the forefoot, midfoot, and hindfoot in young women. Methods Blinded self-controlled clinical trial. The study included 10 women aged 18-30 years with flat feet, as classified by the Foot Posture Index, to improve the homogeneity of the participants. Three-dimensional gait analysis of the 10 women with flatfoot was done without and with elastic tape. It was applied on the side with the greater magnitude of flatfoot (experimental) and the opposite side was used as the control. The Oxford Foot Model was used to assess the foot kinematics. Independent and paired t-tests, and the Wilcoxon and Mann-Whitney tests were used for comparisons. Results Elastic tape did not alter the spatial-temporal gait parameters, such as cadence, gait speed, double-support duration, single-support duration, step length, and step width. The tape did modify the frontal forefoot motion during initial contact, toe-off, and maximum pronation. These differences were confirmed through both intragroup and intergroup comparisons. The tape did alter the arch height and deformation, but these differences were observed only in intragroup comparisons. The tape did not affect the frontal hindfoot motion during the initial contact, toe-off, and maximum pronation. Conclusions The application of the elastic tape altered the frontal forefoot motion in female participants in the short-term. It resulted in improved forefoot supination during the initial contact, toe-off and maximum pronation. The tape did not influence the arch height or the frontal hindfoot motion.